64 STATISTICAL ANALYSIS OF PROGNOSTIC FACTORS AFFECTING LONG-TERM PROGNOSIS AFTER ENDOSCOPIC TREATMENT OF ESOPHAGEAL VARICES. (14th September 2020) - Nishimura, T
Abstract:  : Gastroesophageal varices are present in approximately 50% of patients with cirrhosis, and their rupture is a life-threatening complication. However, mortality rates have declined due to the progress in the management of these patients. Especially advances in endoscopic treatment have contributed to the improved survival rates. In this study, we investigated the prognostic factors associated with long-term survival after endoscopic treatment for esophageal varices. Methods: The subjects were 260 patients who underwent initial endoscopic treatment for esophageal varices in our hospital between January 1997 and June 2019. Among them, 160 successfully followed up. The patients' characteristics were: mean age, 65.4 years (29–85); 109 men and 51 women; and median survival period, 53 months. For analysis, subjects were divided into long-term survival and non-long-term survival groups (n = 59 for each) with a 53-month survival period as a cut-off value. Results: The long-term/non-long-term survival group had a preoperative Child-Pugh score of 6.2 ± 1.1/7.4 ± 2.0 (p < 0.01) and hepatocellular carcinoma (HCC) presence rate was 25.4%/55.9% (p < 0.01), significantly higher in the non-long-term group. Analysis of the factors affecting survival period using Cox proportional hazards model showed that Child-Pugh score B or C [hazard ratio(HR):2.0143, p < 0.05], total bilirubin value≧ 2 [HR:2.5573, p < 0.05], and presence of HCC [HR:2.2450, p < 0.01] were noted as significant factors. Only presence of HCC was found to be a significant factor affecting the long-term survival using multiple logistic regression analysis [odds ratio:0.3463, p < 0.05]. Conclusion: Our study revealed that liver function and the presence of HCC affect long-term prognosis after endoscopic treatment for esophageal varices.